Paleoenvironmental evolution of the Guadiana Estuary, Portugal, during the Holocene: A modern foraminifera analog approach. (February 2017) - Camacho, Sarita; Boski, Tomasz; Moura, Delminda; Scott, David; Connor, Simon; Pereira, Laura
In this paper, we reconstruct the Holocene paleoenvironmental evolution of the Guadiana Estuary, southwestern Iberian Peninsula. Two previously studied boreholes (CM3 and CM5) were revisited and analyzed in the light of a foraminifera modern analog approach. Cluster analyses define four assemblages with different biocenotic, taphonomic, elevation and distance-to-sea settings, which serve as a baseline for paleoassemblages interpretation. Faunal changes along the sedimentary sequences, together with previous sedimentological and chronological data, redefine the different phases of environmental evolution in the Guadiana Estuary since ca. 13 kyr cal. BP, with special emphasis on the Holocene marine highstand. Estuarine flooding began synchronously in both locations (ca. 9 kyr cal. BP) but manifested differently in each sedimentary sequence. The most seaward borehole records a more evident and longer highstand (ca. 8.8–3.8 kyr cal. BP), characterized by the occurrence of subtidal environments and by the presence of open marine species ( Pararotalia cf. spinigera, planktic forms and a significant number of exotic/allochthonous tests), indicating warmer and more marine conditions than today. In the most landward borehole, the highstand is shorter (ca. 8–7.6 kyr cal. BP) and less intense, characterized by the presence of a diverse, mainly autochthonous, open estuary assemblage, dominated by Ammonia aberdoveyensis and Haynesina germanica . At 4.4 kyr cal. BP, during a long deceleration phase of regional sea-level rise, a short but well-defined pulse of marine influence is recorded in CM5, when open estuarine assemblages reappear and replace marsh agglutinated assemblages, suggesting a new submergence phase. This short event is not identified in the previous works carried out in the same area, thus further data are needed to understand whether it is consequent from a global, warming period or whether it resulted only from local and ephemeral forcing effects.